KEPUASAN KONSUMEN DAN LAYANAN PELANGGAN BERPENGARUH TERHADAP KESETIAAN KONSUMEN MELALUI KETERIKATAN KONSUMEN SEBAGAI MEDIA INTERVENING - Edy Saptono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to find out whether consumer attachment affects the loyalty of Holland Bakery consumers, especially in North Cikarang Ruko Plaza Roxy Jababeka in the midst of increasing competition by prioritizing quality, so this study wanted to find out how much influence consumer attachment has on consumer loyalty. This study uses a quantitative approach by distributing questionnaires to 130 respondents. This study uses a probability sampling technique with purposive sampling type based on consumers who have made purchases more than once. This type of research is descriptive research, which is a writing that describes the actual situation about the object under study. The test was carried out using the Structural Equation Model (SEM) supported by the AMOS 2.2 software program and IBM SPSS statistics 22, the results showed that consumer attachment had a positive and significant effect on consumer forfeiture.